THE ROLE OF DEMOGRAPHICS IN NUTRITIONAL SUPPLEMENT PRACTICES: EVIDENCE FROM AHMEDABAD - Rajpurohit, Sajjansingh; Tijoriwala, Roshni (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Health awareness, exercise, and lifestyle changes have driven nutritional supplement demand. Demographic characteristics, information sources, and key supplement motivations are examined in this Ahmedabad research on dietary supplement usage. Research shows that younger people generally trust social media celebrities and fitness coaches for supplement advice, whereas older people seek specialists. Lifestyle and exercise objectives determine supplement selection, with protein powders and multivitamins being the most popular. Potential hazards, side effects, and the importance of medical advice are yet little understood. The research emphasizes the need for stronger laws, consumer education, and healthcare practitioner participation to ensure informed and responsible dietary supplement usage.